Negligible Quantities of Particulate Low‐Temperature Pyrogenic Carbon Reach the Atlantic Ocean via the Amazon River. Issue 9 (14th September 2021) - Häggi, C.; Hopmans, E. C.; Schefuß, E.; Sawakuchi, A. O.; Schreuder, L. T.; Bertassoli, D. J.; Chiessi, C. M.; Mulitza, S.; Sawakuchi, H. O.; Baker, P. A.; Schouten, S.
Abstract: Particulate pyrogenic carbon (PyC) transported by rivers and aerosols, and deposited in marine sediments, is an important part of the carbon cycle. The chemical composition of PyC is temperature dependent and levoglucosan is a source‐specific burning marker used to trace low‐temperature PyC. Levoglucosan associated to particulate material has been shown to be preserved during riverine transport and marine deposition in high‐ and mid‐latitudes, but it is yet unknown if this is also the case for (sub)tropical areas, where 90% of global PyC is produced. Here, we investigate transport and deposition of levoglucosan in suspended and riverbed sediments from the Amazon River system and adjacent marine deposition areas. We show that the Amazon River exports negligible amounts of levoglucosan and that concentrations in sediments from the main Amazon tributaries are not related to long‐term mean catchment‐wide fire activity. Levoglucosan concentrations in marine sediments offshore the Amazon Estuary are positively correlated to total organic content regardless of terrestrial or marine origin, supporting the notion that association of suspended or dissolved PyC to biogenic particles is critical in the preservation of PyC. We estimate that 0.5–10 × 10 6 g yr −1 of levoglucosan is exported by the Amazon River. This represents only 0.5–10 ppm of the total exported PyC and thereby an insignificant fraction, indicating that riverine derived levoglucosan and low‐temperature PyC in the tropics are almost completely degraded before deposition. Hence, we suggest caution in using levoglucosan as tracer for past fire activity in tropical settings near rivers. Plain Language Summary: During plant organic matter burning, most of the carbon is emitted to the atmosphere as CO2, but a fraction is retained as pyrogenic biomass. The chemical composition of pyrogenic biomass depends on fire temperature and allows to differentiate between high and low‐temperature pyrogenic biomass. Here, we analyzed if low‐temperature pyrogenic biomass is preserved during transport in the Amazon River and deposited in western tropical Atlantic sediments. We found that only negligible amounts of low‐temperature pyrogenic biomass reach the Atlantic through riverine transport. While most pyrogenic carbon (PyC) originates in the tropics, our study suggests that only an insignificant fraction of low‐temperature PyC is permanently stored in marine sediments, where it would be removed from the short‐term carbon cycle. Key Points: Only negligible amounts of the source‐specific low‐temperature biomass burning tracer levoglucosan are exported by the Amazon River system Marine sediment levoglucosan yields are controlled by organic carbon content regardless of marine or terrestrial source of organic matter Dust and river derived levoglucosan escape burial in the tropical Atlantic, despite the dominant tropical source of pyrogenic carbon